STRENGTHENING THE ENTREPRENEURIAL SPIRIT AMONG SHARIA BUSINESS ACTORS AT THE DARUL FALLAH ISLAMIC BOARDING SCHOOL, BOGOR - adnani, Latifah; Yuniarti, Yuyun (Journal of Economic Empowerment Strategy (JEES), 2025)
Islamic boarding schools are currently expected to be financially independent to meet the operational costs of the Islamic boarding school. One way that can be done is by establishing a Business Unit, as was done by the Darul Fallah Islamic boarding school in Bogor by establishing PT. Dafa Techno Agro Mandiri which operates in the field of plant breeding using a tissue culture system. Apart from that, Islamic boarding schools are also expected to be a reference in implementing business based on sharia concepts. Problems faced by PT. Dafa 1) Business managers focus on making products and lack an entrepreneurial spirit. The business sector is handed over to the main director, who is busy and often goes abroad. 2) Business planning adapts to government programs, not market conditions. 3) Sharia business practices are not yet implemented in running it. Business. The research objectives are: a) Analyze the entrepreneurial spirit of PT business managers. Dafa b) Knowing the Implementation of Sharia Business at PT. Dafa. Based on the results of research at PT. Dafa Techno Agro Mandiri (PT. Dafa) that 1) The entrepreneurial spirit of company managers still needs to be improved, especially in terms of creativity in carrying out business activities. Because currently the day-to-day company management hands over the business sector to the main director. Managers and employees are focused on producing seeds, according to the direction of the main director. Not yet business oriented. Apart from that, company planning emphasizes government programs, not general market needs. Apart from that, it is also implementing a strategy to improve relations with student alumni, potato breeders and the government to expand the market. 2) Implementation of sharia business for business actors at PT. Dafa Tecno Agro Mandiri has been implemented. But they do not realize that what they are doing already applies sharia principles. Like managers who work sincerely with the intention of worship, not just pursuing material things. Apart from that, when facing business losses, managers and employees accept it with a good opinion of Allah that Allah is the one who regulates the sustenance of His servants.  Competitors are treated as partners. The new concept outlined is that of strengthening the entrepreneurial spirit for sharia business actors, that is, apart from implementing character factors that refer to sharia values, it is also necessary to improve their business spirit. Suggestions for companies 1) We recommend that the entrepreneurial spirit be strongly instilled in all managers and employees. So that business development can be carried out and inspired by all business actors at PT. Dafa . 2) Even though PT. Dafa Teknoagro Mandiri has implemented sharia business in its daily business operations but should be more prominent about the implementation of sharia business in PT companies. Dafa. So it can be used as a reference for Islamic boarding schools and other business actors.